2013
DOI: 10.5006/0875
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Mechanical and Isothermal Low-Cycle Fatigue Behavior of Type 316L Stainless Steel in High-Temperature Water and Air

Abstract: Two unique facilities for isothermal low-cycle fatigue (LCF) and in-phase (IP) or out-ofphase (OP) thermo-mechanical fatigue (TMF) testing of tubular specimens under boiling water reactor (BWR) and pressurized water reactor (PWR) coolant conditions were set up and successfully tested. The systems allow both strain-and stress-controlled fatigue experiments with very small strain amplitudes or complex stress/strain profiles with superimposed rather rapid temperature changes (100 -340 °C) under flowing conditions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…A detailed description of the water loop facility employed for this study can be found in [4]. The load-controlled fatigue tests were performed at 288°C in air and in pressurized water environment characterized by high-purity, deoxygenated (nitrogen purging) water with 150 ppb dissolved hydrogen which is representative of boiling water reactor/hydrogen water chemistry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A detailed description of the water loop facility employed for this study can be found in [4]. The load-controlled fatigue tests were performed at 288°C in air and in pressurized water environment characterized by high-purity, deoxygenated (nitrogen purging) water with 150 ppb dissolved hydrogen which is representative of boiling water reactor/hydrogen water chemistry.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in some cases, dependent on temperature and environment, mean stresses could have significantly beneficial or detrimental effect on the fatigue life of austenitic steels. The effect of mean stress on fatigue life in water environment has been identified as one of the issues that is not sufficiently documented and that needs to be addressed [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The facility for fatigue tests in high-temperature water ( Figure 6) consists of an Instron 8862 electro-mechanical fatigue test machine and a water loop that allows thermo-mechanical loading under BWR or PWR water chemistry conditions. A detailed description of the facility is described in [10]. The fatigue tests were conducted at 288°C and pressurized water was characterized by high-purity, hydrogenated water with 150 ppb dissolved hydrogen (BWR/HWC).…”
Section: Fatigue Test Facilities and Experimental Conditionsmentioning
confidence: 99%